2021
DOI: 10.3390/ijms23010391
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Best Transthyretin Aggregation Protocol to Study Amyloid Fibril Disruption

Abstract: Several degenerative amyloid diseases, with no fully effective treatment, affect millions of people worldwide. These pathologies—amyloidoses—are known to be associated with the formation of ordered protein aggregates and highly stable and insoluble amyloid fibrils, which are deposited in multiple tissues and organs. The disruption of preformed amyloid aggregates and fibrils is one possible therapeutic strategy against amyloidosis; however, only a few compounds have been identified as possible fibril disruptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Human wtTTR was aggregated in vitro into thioflavin T-positive aggregates according to published protocols. 46 , 50 The absorbance, emission, and excitation profiles of AMDX-9101 were then measured in reactions containing 4 µM of AMDX-9101 in solution with and without 5 µM of TTR aggregates, and the fold increase in fluorescence induced by TTR was calculated. The peak fluorescence emission of AMDX-9101 (549 nm) was enhanced approximately 27-fold upon incubation with aggregated TTR, compared to fluorescence in the absence of TTR, while excited at 450 nm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human wtTTR was aggregated in vitro into thioflavin T-positive aggregates according to published protocols. 46 , 50 The absorbance, emission, and excitation profiles of AMDX-9101 were then measured in reactions containing 4 µM of AMDX-9101 in solution with and without 5 µM of TTR aggregates, and the fold increase in fluorescence induced by TTR was calculated. The peak fluorescence emission of AMDX-9101 (549 nm) was enhanced approximately 27-fold upon incubation with aggregated TTR, compared to fluorescence in the absence of TTR, while excited at 450 nm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pure microglial cell cultures were obtained as previously described using a technique that relies on the preferential adhesion of microglial cells to PEI [31,33]. Briefly, brains from postnatal day 1 C57BL/6J mouse pups (Janvier LABS) were removed by dissection, and the meninges were stripped away, after which brain tissue samples were dissociated by repeated pipetting in L15 Leibovitz medium.…”
Section: Neuronal and Glial Cell Culturesmentioning
confidence: 99%
“…TTR is known to transport thyroid hormones (thyroxine and triiodothyronine) and retinol (vitamin A) through binding to the retinol-binding protein (RBP). Tetramer dissociation and partial unfolding of TTR potentiates aggregation [ 45 ] and, therefore, the formation of amyloid fibrils, causing fatal amyloid diseases [ 46 , 47 , 48 ]. TTR amyloid deposits may be associated with wild-type TTR amyloidosis (ATTRwt), a relatively common cardiac disease of aging, but also to several TTR variants linked to hereditary cardiac and neurodegenerative amyloid diseases (ATTRv).…”
Section: Chaperones In Amyloid Disassemblymentioning
confidence: 99%
“…The amyloid systems tested to date with tetracyclines were amyloid-β (Aβ) [ 154 ], α-synuclein [ 155 , 156 ], transthyretin (TTR) [ 46 , 157 , 158 ], β2-microglobulin (β2m) [ 159 ], islet amyloid polypeptide (IAPP) [ 160 , 161 ], immunoglobulin (Ig) light chain (LC) [ 162 ], prion protein (PrP) [ 163 ], and polyQ [ 164 ]. These experiments revealed that tetracyclines are capable of not only completely disassemble amyloid fibrils, but also of blocking assembly into amyloid fibrils, generating non-toxic species after disaggregation, preventing neuronal death and, in some cases, producing clinical benefits in patients affected by amyloidosis.…”
Section: Chaperones In Amyloid Disassemblymentioning
confidence: 99%